The Synergistic Effects of SHR6390 Combined With Pyrotinib on HER2+/HR+ Breast Cancer - Wang, Yukun; Yuan, Xiang; Li, Jing; Liu, Zhiwei; Li, Xinyang; Wang, Ziming; Wei, Limin; Li, Yuanpei; Wang, Xinshuai (Frontiers in Cell and Developmental Biology, 2021)
HER2+/HR+ breast cancer is a special molecular type of breast cancer. Existing treatment methods are prone to resistance; “precision treatment” is necessary. Pyrotinib is a pan-her kinase inhibitor that can be used in HER2-positive tumors, while SHR6390 is a CDK4/6 inhibitor that can inhibit ER+ breast cancer cell cycle progression and cancer cell proliferation. In cancer cells, HER2 and CDK4/6 signaling pathways could be nonredundant; co-inhibition of both pathways by combination of SHR6390 and pyrotinib may have synergistic anticancer activity on HER2+/HR+ breast cancer. In this study, we determined the synergy of the two-drug combination and underlying molecular mechanisms. We showed that the combination of SHR6390 and pyrotinib synergistically inhibited the proliferation, migration, and invasion of HER2+/HR+ breast cancer cells in vitro. The combination of two drugs induced G1/S phase arrest and apoptosis in HER2+/HR+ breast cancer cell lines. The combination of two drugs prolonged the time to tumor recurrence in the xenograft model system. By second-generation RNA sequencing technology and enrichment analysis of the pyrotinib-resistant cell line, we found that FOXM1 was associated with induced resistance to HER2-targeted therapy. In HER2+/HR+ breast cancer cell lines, the combination of the two drugs could further reduce FOXM1 phosphorylation, thereby enhancing the antitumor effect to a certain extent. These findings suggest that SHR6390 combination with pyrotinib suppresses the proliferation, migration, and invasion of HER2+/HR+ breast cancers through regulation of FOXM1.